Making room for impact : a de-implementation guide for educators - Hamilton, Arran, ....-; Hattie, John, ....-; Wiliam, Dylan, ....- (Thousand Oaks : Corwin, 2023)
"This companion book to Building to Impact (BtI) is about stopping, reducing, and/or reversing the initiatives and programs we implement in schools. The authors expand the three-page discussion in BtI into a more comprehensive de-implementation process that they call Making Room for Impact. This is the first book-length de-implementation model in education or healthcare that provides a detailed and rigorous framework, and one that is designed for use at all levels of the system. The 9Ps are DISCOVER: Permit, Prospect, Postulate; DECIDE: Propose, Prepare, Picture; DE-IMPLEMENT: Proceed; RE-DECIDE: Praise, Propel. There are five reasons that educators might seek to get serious, rigorous, explicit, and focused about stopping and de-implementing: 1. To substitute less-effective practices for those that have more evidence and probability for impact 2. To substitute more expensive interventions with those that have the same or better outcomes at a fraction of the cost 3. To adapt practices that have become over-engineered 4. To dial-down the use of a still-needed process 5. To get our lives back"--
Keywords: Education